Implementasi Pendidikan Karakter dalam Perspektif Manajemen Pendidikan Islam di Pondok Pesantren Khas Kempek Cirebon - Sholeh, Moh (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
The urgency of implementing character education in schools or Madrasahs is no longer debated because it has been proven to have great benefits for students, parents and for schools or Madrasahs themselves. However, the implementation in Islamic boarding schools still needs to be researched. The general purpose of this research is to describe how the implementation of character education in the perspective of Islamic education management at the Khas Kempek Islamic Boarding School in Cirebon. The specific objectives of the study, namely describing the planning and implementation of character education at the Khas Kempek Islamic Boarding School, Cirebon Regency, organizing and evaluating in implementing character education as well as what factors are supporting and inhibiting the implementation of character education at the Khas Kempek Islamic Boarding School, Cirebon Regency. The type of research used is qualitative research. The research approach uses phenomenology. The research subjects were Pondok leaders, caregivers, Asatidz, parents and students. Data collection methods using in-depth interviews, observation and documentation. Data analysis techniques using triangulation. The results of the study are planning, organizing, implementing and evaluating education at the Khas Kempek Cirebon Islamic Boarding School as an integral part of other annual activities carried out by schools or Madrasahs in the form of: (a) Preparation and determination of activities to preserve moral values. (b) Awareness and recognition and acceptance of attitudes, behavior, mentality, and morals of school residents carried out in various activities, such as mutual respect and respect for fellow Pondok Leaders, Caregivers, Asatidz, parents of students and fellow students and all residents of the Islamic Boarding School with indicators in the form of changes in attitudes, morals, and mental behavior and their views on the relationship of harmony in social diversity, economic culture, and politics that unify the nation.Keyword: Education Implementation; Character Education; Islamic Education Management.